Scottish migration since 1750 : reasons and results - Docherty, J. C. (Hamilton Books, an imprint of Rowman and Littlefield, 2016)
This work explains Scotland's population and migration history using new methods and unpublished sources. It surveys migration to England, Canada, United States, South Africa, Australia, and New Zealand to 1990.